Children’s Gender Stereotypes in STEM Following a One-Shot Growth Mindset Intervention in a Science Museum - Law, Fidelia; McGuire, Luke; Winterbottom, Mark; Rutland, Adam (Frontiers in Psychology, 2021)
Women are drastically underrepresented in Science, Technology, Engineering and Mathematics (STEM) and this underrepresentation has been linked to gender stereotypes and ability related beliefs. One way to remedy this may be to challenge male bias gender stereotypes around STEM by cultivating equitable beliefs that both female and male can excel in STEM. The present study implemented a growth mindset intervention to promote children’s incremental ability beliefs and investigate the relation between the intervention and children’s gender stereotypes in an informal science learning site. Participants (n =143, female n = 77, n male = 66, 5 – 12-years-old, M age = 8.6, SD =1.7) were visitors to a science museum who took part in an interactive space science show. Participants who were exposed to a growth mindset intervention, compared to the participants in the control condition, reported significantly less gender stereotyping around STEM by reporting equitably in the stereotype awareness measure. Relatedly, participants in the control condition reported male bias gender stereotype in the stereotype awareness measure. Further, children between 5 and 8-years-old reported greater male bias stereotypes awareness and stereotype flexibility in space science compared to children between 9 and 12-years-old. Lastly, children demonstrated in-group bias in STEM ability. Male participants reported gender bias favoring males’ ability in stereotype flexibility and awareness measures, while female participants reported bias towards females’ ability in stereotype flexibility and awareness measures. These findings document the importance of a growth mindset intervention in buffering against STEM gender stereotyping amongst children, as well as the significant role a growth mindset intervention can play within an informal science learning site.